MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) DEVELOPMENT STRATEGY IN THE POST-COVID-19 PANDEMIC PERIOD IN MEDAN TEMBUNG DISTRICT - Muhammad Nur Ridho Siregar; Sirojuzilam; Iskandarini (CV. Radja Publika, 2024)
The MSME strategy in Indonesia is currently considered good considering that the results from MSMEs can help the people's economy, especially reducing unemployment. The existence of micro, small and medium enterprises (MSMEs) constitutes the largest part of the national economy and represents community participation in various sectors of economic activity for a country. This research aims to analyze internal and external factors and to determine the appropriate strategy for developing micro, small and medium enterprises (MSMEs) in the post-Covid-19 pandemic period in Medan Tembung District, Sidorejo Village. This research method is qualitative research using SWOT analysis. The results of this research during the COVID-19 pandemic had a serious impact on MSMEs in Medan Tembung District, Sidorejo Village. Despite receiving government support, MSMEs still face economic uncertainty and intense competition. Post-pandemic business continuity requires implementing internal strategies such as product innovation, human resource development and digital marketing, while paying attention to external support in the form of capital and adaptation to economic changes. Awareness of good management, technology and cooperation between MSME actors is the key to success in maintaining its role as a pillar of a competitive local economy. Strategy for developing micro, small and medium enterprises (MSMEs) in the post-covid-19 pandemic period in Medan Tembung sub-district, based on SWOT analysis, there are 20 alternative strategies that can be implemented, namely 5 (five) SO ( Strengths-Opportunities) strategies, 5 (five) strategies WO (Weaknesses-Opportunities), 5 (five) ST (Strengths-Threats) Strategies and 5 (five) WT (Weaknesses-Threats) Strategies.